Einfluss von Hochleistungssport auf die puberale Entwicklung von weiblichen und männlichen Turnern - Weimann, E.; Witzel, C.; Schwidergall, S.; Bohles, H. J. (Wiener Medizinische Wochenschrift, 1998)
High impact training may influence the pubertal development of athletes. The effects of high intensity training on pubertal development of female and male elite gymnasts are presented. 22 female and 18 male elite gymnasts were enlisted in this study. Prepubertal and pubertal stages were determined and hormonal levels regarding the hypophyseal, gonadal and adrenal axes were measured. The LH/FSH ratio necessary for the advancement of full pubertal maturation was assessed at 13.9 amd 13.0 years in female and male gymnasts, respectively. Female gymnasts demonstrated, on average, a delayed bone age of 1.7 years compared to their chronological age, whereas both bone and chronological age were identical in male gymnasts. There were no significant pubertal increase of estrogen levels in female gymnasts during their peripubertal development indicating a low amount of fat mass in female elite gymnasts. Intensive physical training of elite female gymnasts combined with inadequate nutritional intake markedly affect pubertal development. These peripubertal effects are not observable in male gymnasts due to different training regimes in male and female elite gymnast. Regular monitoring of female gymnast during their vulnerable growth phase is necessary to minimize life-long physiological and psychological side effects of high impact training.